2016
DOI: 10.1016/j.tube.2016.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of serum bradykinin and desArg9-bradykinin levels for chemotherapeutic responses in active tuberculosis patients: A retrospective case series

Abstract: Background There is an urgent need for methods that can rapidly and accurately assess therapeutic responses in patients with active tuberculosis (TB) in order to predict treatment outcomes. Exposure to bacterial pathogens can rapidly activate the plasma contact system, triggering the release of bradykinin (BK) and its metabolite desArg9-bradykinin (DABK) to induce inflammation and innate immune responses. We hypothesized that serum BK and DABK levels might act as sensitive immune response signatures for change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Our group has taken the approach that in order to understand TB pathology we must study lung samples taken from untreated or under-treated TB individuals. Successful antibiotic treatment is known to significantly alter pathology ( 26 30 ). As MTB is killed by the antibiotic, the antigens that stimulate the host immune responses that generate the lung pathology are cleared.…”
mentioning
confidence: 99%
“…Our group has taken the approach that in order to understand TB pathology we must study lung samples taken from untreated or under-treated TB individuals. Successful antibiotic treatment is known to significantly alter pathology ( 26 30 ). As MTB is killed by the antibiotic, the antigens that stimulate the host immune responses that generate the lung pathology are cleared.…”
mentioning
confidence: 99%
“…Higher abundances in the progressor group (Weiner et al, 2018) Glutamine, histidine Lower abundances in the progressor group BK and DABK Serum of 13 HIV-negative adults with microbiologically confirmed active TB TB treatment response Elevated BK and DABK levels after treatment completion (Qian et al, 2016) 12(R)-HETE, 12R-hydroxy-5Z,8Z,10E,14Z-eicosatetraenoic acid; Ac1PIM1, acylphosphatidylinositol mannoside; ADA, adenosine deaminase; BK, bradykinin; DABK, DesArg 9 -bradykinin; CAP, community-acquired pneumonia; GC6-74, the grand challenges in global health GC6-74 project; HIV, human immunodeficiency virus; LAM, lipoarabinomannan; LPI, lysophosphatidylinositol; LTBI, latent tuberculosis infection; MAs, mycolic acids; MPE, malignancy pleural effusion; PG, phosphatidylglycerol; TB, tuberculosis; TPE, tuberculous pleural effusion.…”
Section: Predicts Tb Progressionmentioning
confidence: 99%
“…Instead, the serum contents of des-Arg 9 -BK were reduced during the consolidation phase of treatment. Thus, kinin levels might represent useful biological markers to predict the outcomes of TB treatment [ 20 ]. By using an in vivo model of M. tuberculosis infection, it was demonstrated that splenomegaly increased in B 2 receptor knockout mice, whereas B 1 /B 2 double knockouts presented a reduction of spleen weight [ 73 ].…”
Section: Bacterial Infections and Kininsmentioning
confidence: 99%
“…Additionally, the therapeutic benefits of ACE inhibitors, such as captopril, also rely on the modulation of kinins and their biological effects [ 16 ]. Over the last four decades, the role of either kinin receptor and other components of the kinin system has been described in a series of infectious conditions, such as sepsis, schistosomiasis, leishmaniosis, Chagas Disease, candidiasis, tuberculosis, malaria, and it has been recently correlated with Covid-19 infection [ 17 , 18 , 19 , 20 , 21 , 22 ]. Considering the abovementioned evidence, the present review article aims to discuss the relevance of the kinin system, mainly of kinin receptors, as pharmacological targets for management of infectious diseases, attempting to cover the implication of kinins in the progression of infection-related illnesses in humans.…”
Section: Introductionmentioning
confidence: 99%